Managerial fairness and its effects on employees' job commitment in the nationalised commercial banks of Bangladesh - Ahsan, Ali; Haq, Mahmudul; Jahangir, Nadim (© 2006 Journal of Business Studies, 2017)
This article was published in the Journal of Business Studies [ @ 2006 Journal of Business Studies. ]